Acai, cacao and maca extracts: Anticancer activity and growth inhibition of microbial triggers of selected autoimmune inflammatory diseases - Wang, Xiaohong; Zhang, Jiayu; Cock, Ian Edwin (Pharmacognosy Communications)
Background: The consumption of high antioxidant foods has been linked with a decreased incidence of some cancers and inflammatory diseases. Some high antioxidant foods also inhibit the growth of a variety of bacterial pathogens. Despite this, the high antioxidant ‘superfoods’ acai, cacao and maca are yet to be adequately tested for anticancer activity or the ability to inhibit the growth of bacterial triggers of autoimmune inflammatory diseases. Materials and Methods: Freeze dried acai, cacao and maca powders were extracted and tested for antimicrobial activity using a modi- fied disc diffusion assay and the MICs were determined. Inhibitory activity against CaCo2 and HeLa cancer cell lines was evaluated using colorimetric cell proliferation assays. Toxicity was evaluated using an Artemia francis- cana nauplii bioassay. Results: The acai, cacao and maca extracts dis- played broad spectrum antibacterial activity, inhibiting the growth of all of the bacteria screened, although generally with only low efficacy. The ethyl acetate extracts were more potent bacterial growth inhibitors than were the corresponding methanolic and aqueous extracts. The inhibitory activity of the acai and maca ethyl acetate extracts against P. mirabilis was particularly noteworthy, with MIC values <1000 µg/mL. The aqueous and methanolic extracts of all fruits had only low bacterial growth inhibitory activity. In contrast, the aqueous extracts of cacao and maca were the most effective at inhibiting proliferation of the colorectal cancer cell line CaCo2 (aqueous maca extract IC50=1800 µg/mL) and HeLa cervical cancer cell growth, (aqueous cacao extract IC50 values 1810 µg/mL). All extracts were non-toxic, with LC50 values substantially > 1000 µg/mL. Conclusion: These studies demonstrate that the aqueous cacao and maca extracts have appreciable inhibitory activity against some cancer cell lines and that the acai and maca ethyl acetate extracts were moderate inhibitors of the growth of bacteria associated with selected autoimmune inflammatory disorders. Furthermore, the toxicity studies indicate that they are safe for therapeutic usage. All other extracts were inactive or of low activity towards the cancer and bacterial cells.
Keywords: Euterpe oleracea; Lepidium meyenii; Theobroma cacao; Auto- immune inflammatory disease; Rheumatoid arthritis; Ankylosing spondylitis; Multiple sclerosis; Cancer.